Thymus satureioides Coss.: Mineral Composition, Nutritional Value, Phytochemical Profiling, and Dermatological Properties - Ismail Mahdi; Nidal Fahsi; Hassan Annaz; Badreddine Drissi; Mustapha Barakate; Mona F. Mahmoud; Mansour Sobeh (Molecules, 2023)
Zaitra, Thymus satureioides, is an aromatic plant with a long history of use in traditional medicine. In this study, we assessed the mineral composition, nutritional value, phytocontents, and dermatological properties of the aerial parts of T. satureioides. The plant contained high contents of calcium and iron, moderate levels of magnesium, manganese, and zinc, and low contents of total nitrogen, total phosphorus, total potassium, and copper. It is rich in several amino acids, including asparagine, 4-hydroxyproline, isoleucine, and leucine, and the essential amino acids account for 60.8%. The extract contains considerable amounts of polyphenols and flavonoids (TPC = 118.17 mg GAE/g extract and TFC = 32.32 mg quercetin/g extract). It also comprises 46 secondary metabolites, identified through LC-MS/MS analysis, belonging to phenolic acids, chalcones, and flavonoids. The extract elicited pronounced antioxidant activities, inhibited the growth of P. aeruginosa (MIC = 50 mg/mL), and reduced biofilm formation by up to 35.13% using the ¼ sub-MIC of 12.5 mg/mL. Moreover, bacterial extracellular proteins and exopolysaccharides were diminished by 46.15% and 69.04%, respectively. Likewise, the swimming of the bacterium was impaired (56.94% decrease) in the presence of the extract. In silico, skin permeability and sensitization effects revealed that out of the 46 identified compounds, 33 were predicted to be exempt from any skin sensitivity risk (Human Sensitizer Score ≤ 0.5), while extensive skin permeabilities were observed (Log Kp = −3.35–−11.98 cm/s). This study provides scientific evidence about the pronounced activities of T. satureioides, supports its traditional uses, and promotes its utilization in the development of new drugs, food supplements, and dermatological agents.